Color atlas of animal dermatology - Scott, Danny W. (Oxford, 2007)
A Color Atlas of Farm Animal Dermatology is an essential reference for veterinary dermatologists, practitioners, and students alike. Emphasizing recognition and diagnosis, the book combines over 600 color photographs with clear and concise text highlighting clinical features, differentials, and diagnostic information for each disease. Coverage includes both common and uncommon diseases of cattle, goats, sheep and pigs. The atlas is divided into four species-specific sections for easy reference. Disease types covered include bacterial, fungal, parasitic, viral and protozoal, immunological, congenital and hereditary, environmental, nutritional and miscellaneous diseases, as well as neoplastic and non-neoplastic growths.
Keywords: Livestock,Skin,Veterinary dermatology,Bệnh da liễu,Da; Diseases,Atlases,Diseases,Atlases,Atlases,Bản đồ,Bệnh,Bản đồ